Managerial performance, boards of directors and takeover bidding - Hirshleifer, David; Thakor, Anjan V. (Journal of Corporate Finance, 1994)
This paper models the maintenance of management quality through the simultaneous functioning of internal and external corporate control mechnism—board dismissals and takeovers. We examine how the information sets of the board and the acquiror are noisily aggregated, and how this affects the behaviour of the board and the acquiror. The board of directors, acting ion shareholders' interests will sometimes oppose a takeover, and this opposition can be good news for the firm. An unsuccessful takeover attempt may be followed by a high rate of management turnover, because a takeover attempt conveys adverse information possessed by the bidder about the manager. If there is a probability that the board is ineffective, then a forced resignation of the manager can be either good or bad news for the firm. A positive effect is predicted to dominate when there is more adverse public information avilable about the manager's performance and when there is a higher ex ante probability that the board is ineffective, for example, of the board is management-dominated rather than outsider-dominated.